STUDI POTENSI ASAM LEMAK VOLATIL DARI TANDAN KOSONG KELAPA SAWIT DENGAN FERMENTASI ANAEROB - Andri (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Palm oil is one of the leading commodities, and Indonesia is one of the largest palm oil producers in the world. Oil Palm Empty Fruit Bunches (OPEFB) are the solid waste from palm oil industry activities. The cellulose content in EFB can be used as a substrate for anaerobic decomposition to produce volatile fatty acids (VFAs). In this study, chemical pre-processing (NaOH 8% w / V) was used for the delignification of EFB before being processed in anaerobic fermentation. Digested cow manure (DCM) is used as an inoculum. Process optimization to produce VFAs is a challenge because VFAs are intermediate products in the metabolic pathway of anaerobic decomposition towards methane formation. This study examines the potential of VFAs from EFB by varying the temperature against the EFB anaerobic fermentation process to produce VFAs in batch reactors. The temperature variations studied were mesophilic (29 °C) and thermophilic (55 °C) conditions. Empirical molecular formulas can predict VFA potential with a reaction stoichiometric approach. As a result of the calculation, the VFA potential of EFB is 44.5x10-2 mg.mgTS-1. Experiments showed that thermophilic conditions resulted in VFAs 60% higher than mesophilic, as seen from the percent completion of RT reaching 59% and closer to the theoretical potential.